THE PROBABILITY OF A STRONG (M≥6.0) EARTHQUAKE IN THE SOUTH FERGANA SEISMIC ACTIVITY ZONE IN THE COMING YEARS - R. S. Ibragimov; T. L. Ibragimova; M. A. Mirzaev; Yu. L. Rebetsky (Геодинамика и тектонофизика, 2023)
There were investigated seismic mode and stress state of the Earth’s crust in the South Fergana seismic activity zone. In the central part of the zone, there was identified an area of a long-term seismic quiescence during which no earthquakes with energy class K≥12 (M≥4.5) were recorded. Along the entire length of the seismic quiescence area, there occur an activation of earthquakes of lower energy classes, as well as anomalous fluctuations of the recurrence curve slope. To localize the place of seismic activation probability, the current stress of earth’s crust in the South Fergana seismic activity zone was reconstructed according to focal earthquake mechanisms by the methods of cataclastic analysis of displacements. There were identified the areas with low values of effective confining pressure and maximum shear stresses where strong earthquakes usually occur. Taking into account the stressed state of the Earth’s crust, on the basis of the prognostic parameters of the seismic regime within the South Fergana seismic activity zone there were identified two areas in which M≥6.0 earthquakes may occur in the coming years.